The Multiple Ways Nuclei Scale on a Multinucleated Muscle Cell Scale - Moffatt, Caitlin B. (Dev Cell, 2019)
In mononucleated cells, nuclear size scales with cell size. Whether this relationship extends to multinucleated cells was unknown. In this issue of Developmental Cell, Windner et al. (2019) examine scaling of nuclei in multinucleated Drosophila muscle fibers. They find that nuclear size is affected by global, regional and local factors.